The Influence of Curriculum Based on the Indonesian National Qualifications Framework (KKNI) on the Quality of Student Learning (Studies on Students at the State University of Medan) - Sibarani, Blasius Erik (Pandawan, 2021)
The curriculum is one of the supporting factors of successful learning and of course the curriculum is structured to be able to improve the quality of each student. Currently the current curriculum is being discussed, namely the curriculum based on the Indonesian national qualification framework (KKNI). This curriculum is very closely related to the HOTS system (High Order Thinking Skill), where this system requires students / students to think high-level that requires a variety of different learning and teaching steps by just learning facts and concepts alone. The KKNI curriculum requires students to go directly into the real world / field. This curriculum is also expected to be able to harmonize cognitive, psychomotor, and affective. The purpose of this study was to find out and analyze how the influence of KKNI on the quality of student learning. Data collection techniques are by distributing questionnaires to respondents as many as 40 respondents. The research method used in this study is by using a correlational method that is related to the descriptive method, where the writer will look for the relationship between the variables studied, namely the KKNI towards the quality of student learning. The research approach used by the writer is by using qualitative and quantitative approaches. The results showed that there was an influence of the KKNI curriculum on the quality of student learning. The research method used in this study is by using a correlational method that is related to the descriptive method, where the writer will look for the relationship between the variables studied, namely the KKNI towards the quality of student learning. The research approach used by the writer is by using qualitative and quantitative approaches. The results showed that there was an influence of the KKNI curriculum on the quality of student learning. The research method used in this study is by using a correlational method that is related to the descriptive method, where the writer will look for the relationship between the variables studied, namely the KKNI towards the quality of student learning. The research approach used by the writer is by using qualitative and quantitative approaches. The results showed that there was an influence of the KKNI curriculum on the quality of student learning. Keywords: Curriculum, HOTS, KKNI